Transformasi Akuntansi Syariah di Era Digital sebagai Landasan Transparansi dan Kepercayaan Publik terhadap Lembaga Keuangan Syariah - Ilham Wahyudi; Siti Kadariah; Zaenol Hasan (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2026)
The rapid development of digital technology has brought significant impacts across various sectors, including the Islamic financial industry in Indonesia. Islamic accounting, as a financial reporting system based on Islamic values, is required to adapt to digital transformation in order to maintain its relevance. This article aims to analyze how digital transformation affects Islamic accounting practices and to examine its contribution to enhancing transparency and public trust in Islamic financial institutions. The method employed is a descriptive-conceptual literature review by analyzing various scientific sources, regulations, and official reports from relevant institutions for the period 2015–2025. The findings indicate that the adoption of technologies such as blockchain, artificial intelligence, and cloud computing significantly improves the accuracy, accessibility, and timeliness of Islamic financial reporting. Enhanced transparency through digitalization has been proven to contribute positively to public trust in Islamic financial institutions. Nevertheless, challenges related to human resource readiness, regulatory gaps, and public digital literacy still need to be addressed systematically.